PENDAMPINGAN PENYELESAIAN SENGKETA TANAH OLEH POS BANTUAN HUKUM (POSBAKUM) PERADI DI PENGADILAN NEGERI DENPASAR - Antari, Putu Eva Ditayani; Farhansyach, Muhammad Daffa Figo (Jurnal Abdimas Bina Bangsa, 2024)
Many Indonesian people experience land disputes, not only in rural areas but also in urban areas. The land disputes experienced include various fights over land rights, falsification of land deeds, or the existence of duplicate certificates. These problems are often resolved through non-litigation efforts, especially negotiation and mediation. People rarely take the litigation route to resolve land disputes because of the high court fees charged by the courts, and court decisions are considered not to be executory. Therefore, it is necessary to carry out assistance activities in resolving land disputes prodeo (free of charge) by the legal aid post at the district court. The activity method is carried out by means of preliminary studies and document studies related to land disputes. Next, observe land disputes that occur in district courts. Then, interviews are carried out with parties experiencing land disputes so that they can be assisted in the land dispute judicial process. As a result, people who experience land disputes can get a resolution through a court decision with free court fees (prodeo)